Generative Artificial Intelligence and Public Communication Ethics in Students’ Academic Writing Practices - Agustina, Depi; Rismanto, Malik; Surya, Radin (Blantika: Multidisciplinary Journal, 2025)
The rapid development of generative Artificial Intelligence (AI) has significantly influenced academic practices, particularly in students’ academic writing. This study aims to examine the ethical use of generative AI in students’ academic writing practices in public communication contexts. The research employs a qualitative approach to explore how students utilize AI technologies and how ethical considerations shape their writing behavior. Data were collected through in-depth interviews with 10 key informants and questionnaires distributed to 30 respondents, complemented by direct observations of students who actively use AI tools in their academic writing. The findings reveal that students widely use generative AI to support various stages of the writing process, including idea generation, outlining, language improvement, and content organization. Students perceive AI as a helpful tool that enhances efficiency and productivity in completing academic assignments. However, the study also identifies several ethical concerns, such as the potential overreliance on AI, risks to academic integrity, and the possibility of reduced critical thinking if AI is used without responsible awareness. Furthermore, the results highlight that students with stronger digital literacy and understanding of academic ethics tend to use AI more responsibly, treating it as a supporting tool rather than a replacement for intellectual work. The study emphasizes the importance of establishing ethical guidelines and improving digital literacy in higher education institutions. These efforts are essential to ensure that AI technologies support academic communication while maintaining transparency, originality, and academic integrity in scholarly writing.